The Effect of Exercise and Agility on Speed Dribbling Football Extracurricular MTs Al-Uswah Semarang (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
The The purpose of research to know and analyze: (1) There is the difference of influence dribbling circuit training method and slalom dribbling to dribbling speed of football extracurricular participants MTs Al Uswah Bergas Semarang. (2) There is a difference of influence between participants who have high agility and low to the speed of dribbling football extracurricular participants MTs Al Uswah Bergas Semarang. (3) There is an interaction between the training method and the agility of the dribbling speed of extracurricular participants MTs Al Uswah Bergas Semarang. This research uses an experimental method with a 2x2 factorial design. Data analysis technique uses Analysis of Varian (ANOVA) at significance level (Î±) 0.05. The independent variables in this research are dribbling circuit and slalom dribbling. Agility high and low as attribute variables and the dependent variable is dribbling speed. The results of this study: (1) There is a significant difference effect between dribbling circuit and dribbling slalom dribbling on soccer dribbling speed with significance value (0.009) < Î± (0.05) and Fvalue (8.24) > Ftable (4.04), (2) There is a difference effect between the participants who have high and low agility to the speed of football dribbling where the significance value (0.000) < Î± (0.05) and Fvalue (55.8)> Ftable (4.04), (3) There is an interaction between exercise method and agility to soccer dribbling speed with significance value (0.039) < Î± (0.05) and Fvalue (4.85) > Ftable (4.04).